Future of Supply Chain – Application of Robotics – The Flip Side of It - Vikas Gupta (International Journal of Supply Chain Management, 2023)
Abstract— This research talks about how supply chain management (SCM) is being developed using robotics and process automation, the challenges faced in the transition process, and whether such transition is desirable. While overall efficiency of the SCM process can be improved through the replacement of conventional manual jobs, such as storing, inspecting, sorting, handling, categorizing products, and data entry, the adoption of this cutting-edge technology in areas such as purchase and supply management remains dubious, unpredictable and still relatively unexplored, leaving considerable scope for further research and experimentation.Keywords— RPA, robotic, process, automation, robotic process automation, supply chain, management, SCM